1994
DOI: 10.1093/infdis/170.6.1518
|View full text |Cite
|
Sign up to set email alerts
|

Development Of A Live, Oral, Attenuated Vaccine Against El Tor Cholera

Abstract: Vibrio cholerae El Tor strains from Peru, Bangladesh, and Bahrain were attenuated by deletion of a genetic element that encodes virulence factors and RS1. The B subunit of ctx (ctxB) was reintroduced into the recA gene of the deletion mutants, rendering them unable to recombine with exogenous genetic elements and generating Peru-3, Bang-3, and Bah-3. Fifteen volunteers received one dose of various vaccine strains at 4 x 10(6) to 1 x 10(8) cfu. All strains colonized the gut. A > or = 4-fold rise in vibriocidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
93
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 22 publications
2
93
0
Order By: Relevance
“…Volunteers inoculated with Peru-3 often developed selflimiting diarrhea, whereas diarrhea was not observed in volunteers who received Peru-15 (6,7). Similarly, we found that most (12/18) rabbits inoculated with Peru-3 developed diarrhea, whereas only 2 of 13 rabbits inoculated with Peru-15 exhibited diarrhea.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Volunteers inoculated with Peru-3 often developed selflimiting diarrhea, whereas diarrhea was not observed in volunteers who received Peru-15 (6,7). Similarly, we found that most (12/18) rabbits inoculated with Peru-3 developed diarrhea, whereas only 2 of 13 rabbits inoculated with Peru-15 exhibited diarrhea.…”
Section: Resultssupporting
confidence: 72%
“…Comparative analyses of vaccine candidates suggests that reactogenicity may be linked to V. cholerae's single polar flagellum and/or to bacterial motility. The vaccine strain Peru-3, a ctxA derivative of a Peruvian El Tor clinical isolate, caused diarrhea, whereas Peru-15, a spontaneously derived nonflagellated (nonmotile) derivative of Peru-3, did not (6,7). Both strains engendered protection against challenge with wild-type V. cholerae in human trials, suggesting that the lack of reactogenicity does not simply result from a failure of Peru-15 to colonize.…”
mentioning
confidence: 99%
“…TCP production is essential to the ability of diverse O1 strains of V. cholerae to colonize infant mice (1,30). We therefore tested the four TCP Ϫ , non-O1, non-O139 strains for colonization in infant mice (Table 1), using the CTX Ϫ TCP ϩ O1 strain (Bah-2) as the reference strain (44). Whereas N16961 competed effectively with Bah-2 (competitive index ϭ 1.21), the TCP Ϫ control strain TCP-2 showed an Ϸ10-fold reduction in colonization.…”
Section: Tcp ؊ Non-o1 Non-o139 Strains Are Proficient For Colonizatimentioning
confidence: 99%
“…5,6 Two major strategies have been used to develop a cholera vaccine with long-term immunity: live-attenuated V. cholerae strains lacking the ability to produce CT 5,7,8 and killed whole cell toxogenic V. cholerae strains in combination with CTB. [7][8][9] Several live-attenuated vaccine candidates have been developed including CVD103-HgR, CVD111, CVD101, CVD103, Peru-14, and Peru-15, which have been used in the clinical trials.…”
mentioning
confidence: 99%
“…[7][8][9] Several live-attenuated vaccine candidates have been developed including CVD103-HgR, CVD111, CVD101, CVD103, Peru-14, and Peru-15, which have been used in the clinical trials. 5,6,8,10,11 These are single dose vaccines, which can elicit a high titer of serum vibriocidal antibodies because they can actively colonize the host intestinal lumen. 6,[12][13][14] The major defect of the engineered live vaccine strains is the probability of acquiring the enterotoxin gene through horizontal gene transfer.…”
mentioning
confidence: 99%